Trajectories of Serum Albumin Predict Survival of Peritoneal Dialysis Patients: A 15-year Follow-Up Study. Issue 12 (March 2016) - Chiu, Ping-Fang; Tsai, Chun-Chieh; Wu, Chia-Lin; Yang, Tse-Yen; Liou, Hung-Hsiang; Chen, Hung-Lin; Kor, Chew-Teng; Chang, Chia-Chu; Chang, Horng-Rong
Abstract : Abstract: Although initial serum albumin level is highly associated with overall and cardiovascular mortality in peritoneal dialysis (PD) patients, we consider that the dynamic change and trend of albumin after initiation of PD are also essential. We enrolled patients who received PD for more than 3 months from January 1999 to March 2014. We categorized these patients into 2 groups by the difference in serum albumin level (Δalbumin = difference between peak with initial albumin level = peak albumin level − initial albumin level) after PD. The patients with Δalbumin < 0.2 g/dL (median level) were considered as group A (n, number = 238) and those with Δalbumin ≥ 0.2 g/dL were considered as group B (n = 278). Further, we stratified these patients into quartiles: Q1 Δalbumin < −0.2 g/dL; Q2, −0.2 ≦∼ <0.2 g/dL; Q3, 0.2 ≦∼ <0.6 g/dL; and Q4, ≥0.6 g/dL. Regression analysis was performed to determine the correlation of initial albumin and Δalbumin. Group A patients presented with higher levels of serum albumin (3.71 ± 0.54 vs 3.04 ± 0.55 g/dL; P < 0.001) and hematocrit as well as better initial residual renal function. However, those in group A had lower serum albumin increment and downward-sloped trends after dialysis. In contrast, the albumin trend was upward sloped and the increment of albumin was remarkable in group B, despite the high prevalence of cardiovascular diseases and diabetes. Overtime, group A patients had poorer survival and experienced more frequent and longer hospitalizations. Group Q1 patients with least albumin increment had worst survival. Group Q4 patients with lowest initial albumin also had poor survival. Age, diabetes, cardiovascular diseases, BMI, initial albumin, and Δalbumin could affect patient outcomes independently. Regression analysis showed a better outcome can be obtained if the initial albumin level is at least above 3.15 g/dL. (Initial albumin level = −0.61 × Δalbumin + 3.50.) The increment and trend of albumin especially during early period of PD may be a more crucial determinant for survival.